2021
DOI: 10.1097/nnr.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Parental Worrying, Family Functioning, and Quality of Life During the COVID-19 Pandemic

Abstract: The 2019 novel coronavirus pandemic has affected many aspects of American life, with reported increases in parental anxiety and adverse health outcomes among children. However, it is unknown how family functioning and parental anxiety may be associated with child health outcomes during this pandemic. Objectives:The aim of this study was to explore associations among parental worrying, family functioning, and the health-related quality of life (HRQoL) of middle and high school-aged children in the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Surprisingly and in line with our findings, Taha et al (2022) found that child quality of life during the pandemic was inversely associated with parental education. In that research, they also found that lower levels of parental worrying were related to a better child quality of life.…”
Section: Perceptions Of Play and Families' Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly and in line with our findings, Taha et al (2022) found that child quality of life during the pandemic was inversely associated with parental education. In that research, they also found that lower levels of parental worrying were related to a better child quality of life.…”
Section: Perceptions Of Play and Families' Characteristicssupporting
confidence: 92%
“…As children were older, parents were more likely to agree that they have been doing activities that could negatively influence their global development, and higher frequency of screen time. Increased child age was also associated with a worse quality of life during the pandemic, in Taha et al (2022) findings.…”
Section: Perceptions Of Play and Families' Characteristicsmentioning
confidence: 88%
“…Across studies, higher rates of discord and disrupted family functioning have been identified amongst socially vulnerable family groups, for example, single parents with young children (Rudolph et al, 2021); those experiencing economic stress (Peltz et al, 2021; Westrupp et al, 2021); families with children with neurodevelopmental disabilities (Westrupp et al, 2021) or mental health concerns (Polack et al, 2021); and, families with parental mental illness (Taha et al, 2022; Westrupp et al, 2021; Wu et al, 2021). Lower levels of family cohesion have also been associated with weekly spikes in health-related stress (Peltz et al, 2021), suggesting for some, a relationship between Covid-19 health fears and family functioning.…”
Section: Resultsmentioning
confidence: 99%
“…Not all families reported positive experiences during the pandemic. Some families were more vulnerable than others, including single parents, those experiencing financial stress and unemployment, those with children with special needs or mental health issues and parents with their own pre-existing mental health issues (Polacak, et al, 2021; Peltz et al, 2021; Rudolph et a., 2021; Taha et al, 2022; Westrupp et al, 2021). Mothers in particular bore the brunt of the additional housework and childrearing responsibilities that occurred during the pandemic (Craig & Churchill, 2021; Del Boca, et al, 2021, Evans, et al, 2021; Frank et al, 2021; Gibbons, et al, 2021; Verweij et al, 2021) resulting in negative wellbeing impacts on women, and conflict in the dyad relationship (Craig & Churchill, 2021; Evans, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, having older children (12–18 years) was associated with increased worries of Omicron. A study has shown that increased child age was associated with worse health-related quality of life during the COVID-19 pandemic as assessed by both parents and children [ 39 ]. And given that it may be more difficult for parents to ensure that an older child is protected from infection by the new variant, this may explain the higher worries experienced by parents of teenagers.…”
Section: Discussionmentioning
confidence: 99%